Assessing Teachers’ Readiness in Implementing The 21st Science Teaching Pedagogical Practice: A Cross-Sectional Study in West Kalimantan-Indonesia - Djudin, Tomo (STKIP Singkawang, 2024)
This cross-sectional survey was conducted to assess the level of readiness in implementing 21st century science teaching pedagogical practices among primary, secondary, and high school teachers in West Kalimantan-Indonesia. A total of 365 teachers was drawn as sample consisting of 180 primary, 120 secondary, and 65 senior high school teachers. To assess the teachers’ readiness level by using a Likert scale questionnaire. Based on data analysis, the findings of this research were: (1) The readiness level of implementation of science teaching pedagogical practices by teachers was in moderate category; (2) The level of readiness of senior high school was better than primary and secondary school teachers, the female was better than male teacher, and the senior was better than junior teacher. The supporting and inhibiting factors came from the content, environment, learning materials, teachers, and students. Innovative learning models based on Information and Communication Technology (ICT) need to be continued to build teacher professionalism skills in implementing meaningful science teaching pedagogy in schools.